PERAN GOOD GOVERNANCE MELALUI REFORMASI BIROKRASI DAN E-GOVERMENT GUNA MENINGKATKAN PENYELENGGARAAN PEMERINTAHAN BERBASIS KINERJA DI KOTA SURABAYA - Nely Suwidyanti (Universitas Bina Taruna Gorontalo, 2023)
Therefore, this study aims to determine the relationship between the implementation of good governance based on employment contracts, bureaucratic reform, and E-goverment in order to improve the efficiency of government administration in the city of Surabaya. This research also uses qualitative research methods with data collection techniques in the form of descriptive analytical techniques that are explained or discussed descriptively and based on relevant literature reviews by studying and collecting data taken from articles published in various scientific journals and book collections. The instrument used is secondary data referenced from the relevant literature review. In an effort to improve government administration, Surabaya city conducts bureaucratic reforms based on work contracts where government administrators, such as regional heads, are always required to achieve predetermined work targets. The results of this study indicate that in the implementation of bureaucratic reform to achieve good governance, the Surabaya city government uses the concept of work contracts to run well with the output in the form of work evaluation using the concept of work contracts that utilize technology (e-government) so that it can be more transparent. This is evidenced from several aspects, such as the use of e-government related to the establishment of good governance practices, the implementation of good governance related to bureaucratic institutional reform, there is a relationship between performance and electronic government, performance with bureaucratic reform, and the implementation of good governance with performance.